On the new late B- and early A-type periodic variable stars. Issue Volume 9:Issue S301(2013) (18th February 2014) - Mowlavi, Nami; Saesen, Sophie; Barblan, Fabio; Eyer, Laurent
Abstract: We summarize the properties of the new periodic, small-amplitude, variable stars recently discovered in the open cluster NGC 3766. They are located in the region of the Hertzsprung-Russell diagram between δ Sct and slowly pulsating B stars, a region where no sustained pulsation is predicted by standard models. The origin of their periodic variability is currently unknown. We also discuss how the Gaia mission, launched at the end of 2013, can contribute to our knowledge of those stars.